Sustentabilidade da vida humana e as possibilidades da divisão sexual do trabalho doméstico - Sartor, Angela Kalckmann Romanó (2011)
The sustainability of human life, meaning the activities necessary for the process of social reproduction and life maintenance, as not conceived as productive work has not been treated as a priority for the development of the individual or the society. Performed basically by women in the domestic environment, it is the scene of inequalities and conflicts, in which women who cannot divide responsibilities face a double or triple day work. The object of this research is to know which strategies the working women of Curitiba, holders of a high school diploma, are using to go through this challenge, what services they can be provided and who they can count on. This qualitative and interpretative research has interviewed 15 women and tried to understand the meaning of the gender division of labour i.e. how is domestic work divided between men and women of the same family, and what is the role of the Government and the employer. Their testimonies evidence they are facing times of change and persistency, where the reproductive behaviour coexists with change of values and attitudes. The prevalent model of gender division of labor, defined by Hirata and Kergoat, is the conciliation, although traditional and partnership models also occur in a smaller degree. Grandmothers play a substancial role on the emancipation of the working women. They can count on their own mothers mostly when they cannot get the Government and employer’s support through day-cares for their children. Technological innovations have significantly contributed as time and effort savers for the accomplishment of domestic tasks, but do not quite picture the main focus in the gender division of labour.